Liver Histopathology of Mice Induced by Paracetamol on Administration of Methanol Extract of Laban Tree Bark (Vitex pubescens Vahl.) - Wiwit Anggraini; Diah Wulandari Rousdy; Elvi Rusmiyanto Pancaning Wardoyo (Universitas PGRI Semarang, 2023)
Paracetamol metabolism takes place in the liver mediated by CYP450 enzymes and generates NAPQI radicals. The NAPQI radical is highly electrophilic to hepatocyte biomolecules and is therefore capable of inducing liver damage. Laban tree bark (V. pubescens) methanol extract is known to contain antioxidant compounds of flavonoids, saponins, and tannins with an IC50 value of 19.83 g/ml. This study aims to determine the optimal dose of extract that can improve the liver microanatomy of mice induced by toxic dose of paracetamol (TDP). This study used 30 male Swiss strain mice with a body weight of 20-30 g. The treatments given consisted of negative control (paracetamol 105 mg kg-1), positive control (vitamin E 46.8 mg kg-1), and laban extract at a dose of 75; 150; 300; 600 mg kg-1 BW. Liver microanatomy parameters measured included hepatocyte diameter (19.50±0.21 µm), sinusoids (4.39±0.23 µm), and central vein (36.84 ± 1.79 µm). Data were analyzed using one-way ANOVA and Duncan's Multiple Range Test further test was then presented in the form of mean ± standard deviation. The results showed that extract at a dose of 600 mg kg-1 had hepatocyte, sinusoid, and central vein diameters that were not significantly different (p>0.05) with vitamin E.